Petersburg - Bely, Andrey, 1880-1934; Strasser, Nadja, 1871-1955 (Salt Lake City, UT : Project Gutenberg, 2012)
"Petersburg" by Andrey Bely is a novel written in the early 20th century. It explores the complex lives of its main character, Apollon Apollonowitsch Ableuchow, a senator navigating the tense social and political climate of Russia amidst personal struggles involving his son, Nikolai. The narrative delves into themes of identity, power, and the labyrinthine structure of both government and personal relationships. At the start of the narrative, we are introduced to Apollon Apollonowitsch Ableuchow, a senator of significant standing, who reflects on his lineage and the weight of his political responsibilities. As he prepares for the day, we see his meticulous approach to life and work juxtaposed against hints of dissatisfaction, particularly in his relationship with his son, Nikolai, who is artistically inclined yet seemingly directionless. The opening also establishes a backdrop of St. Petersburg's atmospheric setting, marked by fog and the struggles of its inhabitants, setting a tone that resonates with the complexities of the characters' lives. As the story unfolds, the reader is invited into a deeply introspective exploration of the intertwining fates of father and son within a greater socio-political landscape. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Petersburg_(novel)
Release date is 2012-06-05
Produced by Jens Sadowski
Keywords: Historical fiction; City and town life -- Fiction; Saint Petersburg (Russia) -- Fiction; Russian fiction -- Translations into German; Russia -- History -- Revolution, 1905-1907 -- Fiction